Strategy for laparoscopic repair of inguinal hernia after robot‐assisted radical prostatectomy. Issue 1 (12th September 2021) - Eto, Shohei; Yoshikawa, Kozo; Yoshimoto, Toshiaki; Takasu, Chie; Kashihara, Hideya; Nishi, Masaaki; Tokunaga, Takuya; Nakao, Toshihiro; Higashijima, Jun; Iwata, Takashi; Shimada, Mitsuo
Abstract: Introduction: Robot‐assisted radical prostatectomy (RARP) is nowadays being performed worldwide, and inguinal hernia (IH) continues to be a common complication of radical prostatectomy. Laparoscopic repair of IH is often difficult via internal dissection because of adhesion of the preperitoneal cavity. This study aimed to categorize the intraoperative condition of, and devise a strategy for, IH after RARP. Methods: Of 577 patients who underwent RARP, 18 developed IH. These 18 patients then underwent laparoscopic IH repair using the transabdominal preperitoneal approach (TAPP) or modified intraperitoneal onlay mesh repair (mIPOM). Internal dissection was categorized into two groups according to the appearance of Cooper's ligament (exposed or not exposed). Results: After RARP, four patients had exposure of Cooper's ligament while 14 patients showed no exposure. Both patients in the exposed group underwent TAPP and all patients in the not‐exposed group underwent mIPOM. There was no significant difference between normal TAPP and RARP regarding operative factors, and IH recurrence was not observed. Conclusion: Laparoscopic repair of IH after RARP is rendered safe and efficient by using our categorization based on the exposure of Cooper's ligament and extension of preperitoneal space.